Aiming to increase birth weight: a randomised trial of pre-pregnancy information, advice and counselling in inner-urban Melbourne - Donohue Lisa; Lumley Judith (BMC, 2006)
Abstract Background In the 1980s there was substantial interest in early pregnancy and pre-pregnancy interventions to increase birth weight and reduce preterm birth. We developed an inter-pregnancy intervention, implemented in a randomised controlled trial, to be provided by midwives at home soon after women's first birth. Methods MCH nurses invited women to take part during their home visit to new mothers. Women's contact details, with their permission, were passed to the study midwife. She had a randomisation schedule to which women's names were added before she met the women or their partners. All women recruited had a home visit from the study midwife with a discussion of their first pregnancy, labour and birth and the postpartum experience. Women in the intervention arm received in addition a pre-pregnancy intervention with discussion of social, health or lifestyle problems, preparation and timing for pregnancy, family history, rubella immunisation, referrals for health problems, and a reminder card. The primary outcome was defined as a birth weight difference in the second birth of 100 g (one-sided) in favour of the intervention. Additional data collected were gestational age, perinatal deaths and birth defects. Analyses used EPI-INFO and STATA. Results Intervention and comparison groups were comparable on socioeconomic factors, prior reproductive history and first birth outcomes. Infant birth weight in the second birth was lower (-97.4 g,)) among infants in the intervention arm. There were no significant differences between intervention and comparison arms in the proportion of women having a preterm birth, an infant with low birthweight, or an infant with a birth weight <10th percentile. There were more adverse outcomes in the intervention arm: ten births <32 weeks), compared with one in standard care, and more infants with a birth weight <2000 g, 16 compared with two in standard care Conclusion As the primary outcome was envisaged to be either improved birth weight or no effect, the study was not designed to identify the alternative outcome with confidence. Despite widespread support for pre-pregnancy interventions to improve maternal and perinatal health, this first randomised controlled trial of a multi-component intervention provided at home, did not have a beneficial outcome.